Patients with symptomatic uncomplicated diverticular disease have high fecal bile acid concentrations - Jono, Tsumugi; Kasai, Yuki; Kessoku, Takaomi; Tanaka, Kosuke; Iwaki, Michihiro; Kobayashi, Takashi; Takahashi, Kota; Seita, Kosuke; Kato, Takayuki; Sakai, Eiji; Kurihashi, Takeo; Nakatogawa, Machiko; et al. (Frontiers in Medicine, 2025)
Background and AimSymptomatic uncomplicated diverticular disease (SUDD) causes persistent pain and impairs patient quality of life; however, its pathogenesis remains unknown. This study investigated the relationship between SUDD and the inflammatory effects of intestinal bile acids (BAs).MethodsFive institutional cohorts with 361 total patients who received outpatient treatment for abdominal symptoms (from 2020 to 2022) were included in this prospective cohort study. All patients underwent colonoscopy. SUDD was defined as the presence of recurrent abdominal symptoms—pain in the lower quadrant lasting >24 h—in patients with diverticulosis at the site of pain. Patients with diverticula were classified into SUDD and non-SUDD groups. The healthy control (HC) group comprised people with no history of medications and no evidence of colonic diverticula. Liquid chromatography-mass spectrometry determined the concentration of fecal BAs. Fecal calprotectin and blood endotoxin activity assay (EAA) levels were measured.ResultsTotal fecal BA concentrations did not differ between HC and non-SUDD patients; however, BA levels were significantly higher in patients with SUDD. Fecal calprotectin and blood EAA levels were significantly higher in the SUDD and non-SUDD groups than in the HC group, and in the SUDD group than in the non-SUDD group. Total BA was mildly positively correlated with fecal calprotectin and blood EAA.ConclusionFecal BA concentrations were significantly increased in patients with SUDD compared with patients without SUDD or healthy subjects, suggesting that fecal BAs might be involved in the pathogenesis of SUDD and that controlling fecal BA levels may be therapeutic for SUDD.